Distinctive analysis of the shear bond strength of Porcelain Fused Metal substructure fabricated by conventional casting, direct metal Laser Sintering and CAD-CAM processing techniques: Shear bond strength of PFM Substructure fabricated by conventional casting, direct metal Laser Sintering and CAD-CAM Techniques - Usharani, R; Kothuri, Ravalika N; Daram, Tejasvi (International Journal of Dental Materials, 2022)
Background: The use of metal-ceramic restorations began in the late 1950’s allowing the development of prosthetic rehabilitation with better cosmetic results replacing previously in-demand precious metals. These restorations are commonly prepared using conventional casting, Direct Metal Laser Sintering and CAD-CAM processing techniques. The present study has been attempted to perform a distinctive analysis of the shear bond strength of porcelain fused metal substructure fabricated by conventional casting, Direct Metal Laser Sintering and CAD-CAM processing techniques.Materials and Methods: The present study follows an in-vitro study design. A total of 45 samples were prepared and divided into 3 groups (n=15 in each group): conventional casting, Direct Metal Laser Sintering and CAD-CAM groups. The shear bond strength of all the specimens was measured using Universal Testing Machine. The specimens were subjected to shear load at the metal-porcelain interface with increasing load and the crosshead speed of 2 mm/sec till the disc debonded completely. The debonded samples were observed under Scanning Electron Microscope to assess the kind of failure.Results: The obtained data of three experimental group samples were analysed using the student’s t-test, One-way ANOVA test and Tukey’s Post-hoc test. Results of t-test showed that, of all the three techniques, Casting technique shows highest mean of force and shear bond strength, and this mean difference was significant. The same results were shown in One way ANOVA test and Tukey’s Post-hoc test.Conclusion: From the observations of the present study, it can be stated that Casting technique showed highest mean of load and shear bond strength followed by the CAD/CAM method and DMLS technique, respectively. The results of this study ranged from 69-87MPa which is within the safety borders. Therefore, it can be concluded that all three methods can be used to fabricate the metal substructure in metal-ceramic restoration.Keywords: CAD-CAM, Casting, Direct Metal Laser Sintering, Shear bond strength.